Controlled Growth and Up‐Conversion Improvement of Sodium Yttrium Fluoride Crystals. Issue 8 (10th January 2013) - Fu, Junxiang; Fu, Xionghui; Wang, Chaomin; Yang, Xianfeng; Zhuang, Jianle; Zhang, Gongguo; Lai, Boyuan; Wu, Mingmei; Wang, Jing
Abstract: A variety of hexagonal sodium yttrium fluoride (NYF) crystals with tunable shapes have been grown, and their up‐conversion (UC) emission has been greatly improved after post‐treatment in an aqueous solution of NH4 HF2 and NaF. The enhancement has been attributed to topotactic ion insertion of sodium cations into the channels of Na3 x Y2– x F6 . As sodium‐ion insertion continues to occur and the sodium content rises, the up‐conversion emission intensity and green‐to‐red ratio increase up to the saturation level. However, the X‐ray diffraction patterns and SEM images suggest that both the crystallographic structure and geometric morphology remain unchanged during this topotactic sodium ion insertion. This strategy is very different to previous reports on the use of ion exchange in the preparation of sodium yttrium fluoride crystals and improvement of UC emission. The results of this work demonstrate that sodium vacancy in the hexagonal Na3 x Y2– x F6 crystal is the key to the clear reduction in the up‐conversion photoluminescence properties of the crystals, but the topotactic sodium ion insertion can revive the up‐conversion efficiency greatly. Abstract : Hexagonal sodium yttrium fluoride (NYF) crystals with rich morphologies have been grown by a rational route. Their up‐conversion emission can be improved by post‐treatment, but the as‐grown crystal shapes can be preserved. This has been attributed to topotactic sodium ion insertion into the channels of the hexagonal sodium yttrium fluoride framework.